Facile synthesis of porous Pd3Pt half‐shells with rich "active sites" as efficient catalysts for formic acid oxidation - Yan, Xiaoxiao (2020)
Exploring highly efficient electrocatalysts is greatly important for the widespread uptake of the fuel cells. However, many newly generated nanocrystals with attractive nanostructures often have extremely limited surface area or large particle-size, which leads them to display limited electrocatalytic performance. Herein, a novel anode catalyst of hollow and porous Pd3 Pt half-shells with rich "active sites" is synthesized by using urea as a guiding surfactant. It is identified that the formation of Pd3 Pt half-shells involves the combination of bubble guiding, in situ deposition of particles and bubble burst. The obtained Pd3 Pt half-shells demonstrate a rich edge area with abundant exposed active sites and surface defects, indicating great potential for the electrocatalysis. When used as an electrocatalyst, the Pd3 Pt half-shells exhibit remarkably improved electrocatalytic performance for formic acid oxidation (FAO), where it promotes the dehydrogenation process of FAO by suppressing the formation of poisonous species COads via the electronic effect and ensemble effect.